Working with strengths : putting personalisation and recovery into practice - Morgan, Steve (Pavilion Publishing and Media Ltd, 2014)
The language in health and social care is littered with references to person-centred care, person-centred planning, personalisation, self-directed support, recovery and enablement. However, there remains a degree of confusion between service users, carers, practitioners, managers and commissioners about the practical delivery of these concepts in daily practice. A consistent theme throughout all of these concepts is the need to identify and work with people's strengths (ie. their abilities, capabilities, qualities, motivations, wants and aspirations). This book will elaborate why and how we work with strengths alongside the more usual focus on problems and deficits.